1999
DOI: 10.3354/meps177189
|View full text |Cite
|
Sign up to set email alerts
|

210Po binding to metallothioneins and ferritin in the liver of teleost marine fish

Abstract: The subcellular distribution of the naturally occurring radionuclide "' PO was investigated in the Liver of the Atlantic mackerel Scomber scombrus. The majority of the 2'0Po was found in the cytosol of the liver cells. Fractionation of the cytosol proteins by high performance size-exclusion and ion-exchange chromatography indicated that about 30% of 210Po was bound to ferritin and approximately 28% to metallothioneins. The affinity of 210Po for these proteins was confirmed by a similar binding of the artificia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…Many reports have been published with respect to the tissue-specific function of ferritin, such as the mantle ferritin involved in shell formation in pearl oyster [18]. It has also been suggested that ferritin has other functions, including roles in invertebrate immune responses [35], protection against free radicals [36], cell proliferation [37], and high level accumulation of natural radionuclide 210 Po [17,38,39]. Therefore, having two different ferritin subunits, as well as high levels of expression in certain important organs, gives us a high degree of confidence stating that abalone ferritin has other, unknown functions which warrant future investigation.…”
Section: Discussionmentioning
confidence: 97%
“…Many reports have been published with respect to the tissue-specific function of ferritin, such as the mantle ferritin involved in shell formation in pearl oyster [18]. It has also been suggested that ferritin has other functions, including roles in invertebrate immune responses [35], protection against free radicals [36], cell proliferation [37], and high level accumulation of natural radionuclide 210 Po [17,38,39]. Therefore, having two different ferritin subunits, as well as high levels of expression in certain important organs, gives us a high degree of confidence stating that abalone ferritin has other, unknown functions which warrant future investigation.…”
Section: Discussionmentioning
confidence: 97%
“…This distribution may be different in crustaceans; other authors have shown an important fixation of 210 Po in the microsomal fraction in the lobster hepatopancreas (Heyraud et al 1987). On the other hand, in mackerel liver at the cytosolic level, the distribution of 210 Po is approximately equivalent between metallothioneins and ferritin (28 and 30% of fixation, respectively), so obviously ferritin is not the only binding site at the cellular level (Durand et al 1999).…”
Section: Sephacryl S300 Fractionsmentioning
confidence: 99%
“…metallothioneins and ferritin (Durand et al 1999). The principal aim of this study was to compare the ability of ferritin from different marine organisms to accumulate 210 Po.…”
Section: Introductionmentioning
confidence: 99%
“…210 Po is quickly scavenged out of the surface layer, leading to estimated residence times in surface waters of approximately 0.6 yr (Bacon et al 1976;Cochran et al 1983), a value that is about half its residence time in deeper waters (Kadko et al 1987). 210 Po concentrates appreciably in marine animals (Heyraud and Cherry 1979;Bulman et al 1995;Dahlgaard 1996;Durand et al 1999), providing the largest radiation doses to aquatic organisms. The concentration of 210 Po is Ն148 mBq g Ϫ1 in phytoplankton (Cherry 1964), 3,145 mBq g Ϫ1 in shrimp hepatopancreas (Cherry and Heyraud 1981), Յ700 and Յ1,026 mBq g Ϫ1 in mussel soft tissues (Germain et al 1995) and hepatopancreas (Stepnowski and Skwarzec 2000), respectively, and Յ262 mBq g Ϫ1 in fish (pyloric caecum, Clulow et al 1998).…”
mentioning
confidence: 99%